2011
DOI: 10.2174/1875043501104010039
|View full text |Cite
|
Sign up to set email alerts
|

Wharton's Jelly Stem Cells as Agents for Cancer Therapy

Abstract: Stem cell based therapy has significant potential to treat various diseases including primary and metastatic cancers. The umbilical cord matrix stem cells (UCMSC) derived from human umbilical cord Wharton's jelly (also termed WJMSC) have been shown to exhibit low immunogenicity, which potentially negates immune consequences after cytotherapy. The homing ability of human and rat UCMSC to inflammatory tissues, including cancer tissues, further confers upon these cells the potential for targeted cancer therapy. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Previous studies have demonstrated the capacity of un-engineered human and rat UCMSCs to attenuate amplification of multiple cancer cells in vivo and in vitro Ganta et al 2009). Tamura et al (2011) also reported intrinsic stem celldependent regulation of cancer growth, probable mechanisms underlying the observed biological function, delivery of exogenous anti-cancer agents, and potential clinical applications. By showing intrinsic ability to secrete factors that can inhibit cancer cell growth and/or apoptosis in vitro and in vivo, UCMSC may have several advantages for cell-directed cancer therapy.…”
Section: Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated the capacity of un-engineered human and rat UCMSCs to attenuate amplification of multiple cancer cells in vivo and in vitro Ganta et al 2009). Tamura et al (2011) also reported intrinsic stem celldependent regulation of cancer growth, probable mechanisms underlying the observed biological function, delivery of exogenous anti-cancer agents, and potential clinical applications. By showing intrinsic ability to secrete factors that can inhibit cancer cell growth and/or apoptosis in vitro and in vivo, UCMSC may have several advantages for cell-directed cancer therapy.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Some evidence reported UCMSCs may stimulate caspase activities and arrest cell cyle even in the absence of direct contact with cancer cells. Microarray analysis of rat UCMSCs also revealed over-expression of multiple tumor suppressor genes (Tamura et al 2011). The second mechanism may involve enhancement of an immune reaction to cancer cells.…”
Section: Cancer Therapymentioning
confidence: 99%
“…Specific markers of the endothelial lineage, such as CD31 and vWF [40][41][42][43] are absent in BM-MSCs, as well as hematopoietic markers (CD14, CD34, CD45, CD79, CD86, and glycophorin A-CD235a) [44,45]. Various reports suggested that the use of MSCs in vivo should be safer with respect to formerly investigated embryonic stem cells (ESCs), since MSCs have higher chromosomal stability and do not induce neoplasm formation in the recipient host [46][47][48]. However, only a minor fraction of BM cells are useful for regenerative medicine applications (their frequency ranging between 0,0001% to 0,01% of nucleated cells) [49].…”
Section: Phenotypical Characterization and Imm-unological Features Ofmentioning
confidence: 99%
“…Another key application of WJC is their possible use as anti-cancer agents, and the relevant literature is reviewed by Tamura and co-workers in their review [9]. This is a striking point in MSC biology, since these cells show a clear in vivo tropism for organs which are site of a damage or wound.…”
mentioning
confidence: 99%